Determinants of Fraud Prevention in Village Fund Allocation with Religiosity as a Moderating Variable - Nurfadilah; Dini Nurpratiwi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the determinants of fraud prevention in the management of village fund allocations by considering religiosity as a moderating variable. The variables examined include community participation, the competence of village officials, and the local cultural value of Siri’ na Pacce. This quantitative study was conducted using questionnaires distributed to 87 village officials in Luwu Regency. The data were analyzed using Structural Equation Modeling (SEM) with PLS 4 software.The results show that community participation, the competence of village officials, and the value of Siri na Pacce have a positive effect on fraud prevention in village fund management through increased transparency, accountability, social control, and ethical behavior. In contrast, religiosity does not moderate these relationships, as external monitoring mechanisms, professional factors, and local cultural values are sufficiently strong to prevent fraud without additional reinforcement from religiosity. These findings highlight the importance of strengthening transparency, enhancing the capacity of village officials, and integrating local cultural values into village financial governance to create a more accountable and fraud-free management system. Keywords: Fraud Prevention, Community Participation, Competence, Siri’ na Pacce, Religiosity